On practice and institution : theorizing the interface - Lounsbury, Michael; Anderson, Deborah A.; Spee, Paul (Research in the sociology of organizations ;, 2021)
The concepts of practice and institution are of longstanding importance across the social sciences. This double-volume builds directly on the scholarship of Theodore Schatzki and Roger Friedland, to map out new theoretical and empirical directions at the interface between the practice and institutional "logics" literatures in organizational sociology, bridging the two perspectives. Volume 70 of Research in the Sociology of Organizations focuses on theoretical development including two major, and complementary, theoretical statements by Schatzki and Friedland that engage key ontological issues which lay the groundwork for how their approaches to practice and institutions can be generatively connected.